Change in baseline characteristics over 20 years of adults with growth hormone (GH) deficiency on GH replacement therapy. Issue 6 (December 2019) - Höybye, Charlotte; Burman, Pia; Feldt-Rasmussen, Ulla; Hey-Hadavi, Judith; Aydin, Ferah; Camacho-Hubner, Cecilia; Mattsson, Anders F
Abstract : Objective: Clinical observations over time of adults with growth hormone (GH) deficiency (GHD) have indicated a shift in patient characteristics at diagnosis. The objective of this study was to compare baseline characteristics of patients diagnosed with adult-onset GHD naive to GH replacement during three study periods (1994–1999 (P1), 2000–2004 (P2), and 2005–2012 (P3)) using the KIMS (Pfizer's International Metabolic) database. Methods: Data were retrieved for a total of 6069 patients with adult-onset GHD from six countries (Belgium, Germany, Netherlands, Spain, Sweden, and UK): P1 ( n = 1705), P2 ( n = 2397), and P3 ( n = 1967). Results: The proportions of patients with pituitary/hypothalamic tumors and patients with multiple pituitary hormone deficiencies decreased per entry year period, while the proportions with hypertension and diabetes increased. The lag time from diagnosis of pituitary disease to start of GH treatment decreased by 2.9 years over the entry year periods. IGF-1 increased by 0.1 standard deviation score per entry year period. Maximum GH following various stimulation tests, BMI, and waist circumference increased. The use of radiotherapy, glucocorticoid replacement doses, and the proportion of women >50 years on estrogen replacement therapy decreased. The effects of 1 year of GH replacement were similar over the entry year periods despite changes in the patients' baseline characteristics. An expected increase in fasting blood glucose was seen after 1 year of GH treatment. Conclusions: The degree of confirmed GHD became less pronounced and more patients with co-morbidities and diabetes were considered for GH replacement therapy, possibly reflecting increased knowledge and confidence in GH therapy gained with time.